An integrated strategy for discovering effective components of Shaoyao Gancao decoction for treating neuropathic pain by the combination of partial least-squares regression and multi-index comprehensive method. (5th October 2020) - Feng, Li-Mei; Chen, Yan-Yan; Xu, Ding-Qiao; Fu, Rui-Jia; Yue, Shi-Jun; Zhao, Qi; Huang, Yu-Xi; Bai, Xue; Wang, Mei; Xing, Li-Ming; Tang, Yu-Ping; Duan, Jin-Ao
Abstract: Ethnopharmacological relevance: Neuropathic pain, the incidence of which ranges from 5 to 8% in the general population, remains challenge in the treatment. Shaoyao Gancao decoction (SGD) is a Chinese classical formula used to relieve pain for thousands of years and has been applied for neuropathic pain nowadays. However, the effective components of SGD for the treatment of neuropathic pain remains unclear. Aims of study: To investigate the effect and potential mechanism of SGD against neuropathic pain and further reveal the effective components of SGD in the treatment of neuropathic pain. Materials and methods: Spared nerve injury (SNI) model rats of neuropathic pain were orally given SGD to intervene, the components in vivo after SGD administration were determined, behavior indicators, biochemical parameters, and metabolomics were applied for assessing the efficacy. Then correlation between components and biomarkers was analyzed by pearson correlation method. To further measure the contribution of components to efficacy, the combination of partial least-squares regression (PLSR) and multi-index comprehensive method was carried out, according to the corresponding contribution degree of the results, the components with large contribution degree were considered as the effective components. Results: SGD exhibited a significant regulatory effect on neuropathic pain, which could increase the pain threshold and decrease the levels of SP, β-EP, PGE2 and NO. With the high resolution of UPLC-Q-TOF/MS technology, a total of 128 compounds from SGD were identified and 44 of them were absorbed in blood. Besides, 40 serum biomarkers were identified after intervention of SGD and the metabolic pathways were constructed. The key metabolic pathways including Glycerophospholipid metabolism, Linoleic acid metabolism, Alpha-linolenic acid metabolism, Glycosylphosphatidylinositol-anchor biosynthesis and Arachidonic acid metabolism may be related to the regulation of neuropathic pain. Metabolomics combined with PLSR and multi-index comprehensive method was utilized to discover 5 components including paeonol, DL-Arabinose, benzoic acid, hispaglabridin A and paeonilactone C as effective components of SGD in the treatment of neuropathic pain. This strategy was used to explore the effective components of SGD and elucidate its possible analgesic mechanism. Conclusion: This study demonstrate that SGD significantly relieved neuropathic pain and elucidated the effective components of SGD for treating neuropathic pain, the strategy as an illustrative case study can be applied to other classical formula and is beneficial to improve the quality and efficacy. Graphical abstract: Image 1